Selective carbon-carbon bond activation of epoxides by a bisphosphine Pt(0) complex - Neumann, Susanne Maria; Rominger, Frank (Organometallics, 2019)
Contrasting established bond activation chemistry of oxiranes (epoxides), the unprecedented insertion of a Pt(0) complex into the carbon-carbon bonds of ethylene oxide and other epoxides, generating 3-oxaplatinacyclobutanes under remarkably mild conditions, has been found. Pt(II) neopentyl hydride complex (dtbpm-κ2P)Pt(Np)H (1) undergoes first-order reductive elimination of neopentane at ambient temperature in solution, forming a highly reactive species of an overall composition [(dtbpm)Pt(0)] (C). This intermediate inserts into epoxide C-C bonds or, in the absence of substrates, dimerizes to d10-d10 Pt(0) species D. The epoxide activation products have been fully characterized including X-ray structure determinations. Various experiments have been conducted in order to decipher mechanistic details of this unusual chemistry. Theoretical studies on various levels do not allow a reliable conclusion as to the actual nature of the reactive intermediate C. Both conceivable structures C1 (ring-opened [(dtbpm-κ1P)Pt(0), d10-ML, 12 VE]) and C2 (chelate, [(dtbpm-κ2P)Pt(0)], d10-ML2, 14 VE) are minimum-energy structures with a very small (method-dependent) energy difference.